A meaning-making model of post-migration growth for mainland Chinese university students in Hong Kong. (March 2019) - Pan, Jia-Yan; Ye, Shengquan; Chen, Chen; Park, Crystal
Abstract: Studies of stress-related growth have demonstrated the central role of meaning-making processes in the occurrence of growth following stressful life experiences, but few have examined its role in the context of acculturation. This study developed and tested a meaning-making model of post-migration growth using bootstrap-based mediation analysis with a sample of 489 mainland Chinese university students in Hong Kong. The data were collected through an online cross-sectional survey. The results showed that acculturative stressor was a significant risk factor and that sense-making coping and core belief re-examination acted as significant protective factors for post-migration growth. Sense-making coping and core belief re-examination, in sequence, partially mediated the relationship between acculturative stressor and post-migration growth. This model demonstrates the importance of the cognitive processing of meaning-making in Chinese students' post-migration growth.